2016
DOI: 10.3389/fimmu.2016.00613
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Trafficking through Lymphatic Vessels

Abstract: T cell migration within and between peripheral tissues and secondary lymphoid organs is essential for proper functioning of adaptive immunity. While active T cell migration within a tissue is fairly slow, blood vessels and lymphatic vessels (LVs) serve as speedy highways that enable T cells to travel rapidly over long distances. The molecular and cellular mechanisms of T cell migration out of blood vessels have been intensively studied over the past 30 years. By contrast, less is known about T cell trafficking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 153 publications
(283 reference statements)
1
115
0
Order By: Relevance
“…LV may also regulate immune cell trafficking to HF areas, although immune privilege areas are normally devoid of LV (Paus et al, 2003). Indeed, it has been recently reported that Foxp3 + T regulatory cells, which traffic through LV (Hunter et al, 2016), localize to HF, and regulate HFSC proliferation (Ali et al, 2017). Perifollicular macrophages have also been shown to contribute to the activation of HFSC through the expression of Wnt ligands (Castellana et al, 2014), and myeloid Wnt ligands regulate the development of LV (Muley et al, 2017).…”
mentioning
confidence: 99%
“…LV may also regulate immune cell trafficking to HF areas, although immune privilege areas are normally devoid of LV (Paus et al, 2003). Indeed, it has been recently reported that Foxp3 + T regulatory cells, which traffic through LV (Hunter et al, 2016), localize to HF, and regulate HFSC proliferation (Ali et al, 2017). Perifollicular macrophages have also been shown to contribute to the activation of HFSC through the expression of Wnt ligands (Castellana et al, 2014), and myeloid Wnt ligands regulate the development of LV (Muley et al, 2017).…”
mentioning
confidence: 99%
“…LV may also regulate immune cell trafficking to HF areas, although immune privilege areas are normally devoid of LV (Paus et al, 2003). Indeed, it has been recently reported that Foxp3 + T regulatory cells, which traffic through LV (Hunter et al, 2016), localize to HF and 15 regulate HFSC proliferation (Ali et al, 2017). Perifollicular macrophages have also been shown to contribute to the activation of HFSC through the expression of Wnt ligands (Castellana et al, 2014), and myeloid Wnt ligands regulate the development of LV (Muley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The most well-studied cell types are DCs and T cells, which we will briefly review here. For more extensive reviews we refer the reader to several excellent review articles [28][29][30][31].…”
Section: Lymphatic Transport Of Leukocytesmentioning
confidence: 99%
“…NP-based vaccines were shown to delay the growth of B16-F10 mouse melanomas with enhanced efficacy compared to control free Ag and adjuvant mixtures [150,166]. Guo et al used ~150 nm erythrocyte membrane-enveloped PLGA NPs to simultaneously deliver the human gp100 [25][26][27][28][29][30][31][32][33] melanoma peptide and MPLA [148]. The NPs were found to both persist at the skin injection site and be drained to local LNs, indicating a mixed pattern of NP uptake by skin and LN-resident APCs, which is consistent with the >100 nm particle size [148].…”
Section: Lymphatic-targeting Vaccines For Cancer Immunotherapymentioning
confidence: 99%